Routine testing of close contacts of confirmed COVID-19 cases – National COVID-19 Contact Management Programme, Ireland, May to August 2020. (January 2021) - Carroll, C.; Conway, R.; O'Donnell, D.; Norton, C.; Hogan, E.; Browne, M.; Buckley, C.M.; Kavanagh, P.; Martin, J.; Doyle, S.
Abstract: Objectives: The objective of this study was to inform public health practitioners who are designing, adapting and implementing testing and tracing strategies for Coronavirus disease (COVID-19) control. Study design: The study design is monitoring and evaluation of a national public health protection programme. Methods: All close contacts of laboratory-confirmed cases of COVID-19 identified between the 19th May and 2nd August were included; secondary attack rates and numbers needed to test were estimated. Results: Four thousand five hundred eighty six of 7272 (63%) close contacts of cases were tested with at least one test. The secondary attack rate in close contacts who were tested was 7% (95% Confidence Interval [CI]: 6.3 – 7.8%). At the 'day 0' test, 14.6% (95% CI: 11.6–17.6%) of symptomatic close contacts tested positive compared with 5.2% (95% CI: 4.4–5.9%) of asymptomatic close contacts. Conclusions: The application of additional symptom-based criteria for testing in this high-incidence population (close contacts) is of limited utility because of the low negative predictive value of absence of symptoms. Highlights: More asymptomatic close contacts were identified than symptomatic close contacts. Application of symptom-based criteria for testing in this high-incidence population is of limited utility. The secondary attack rate in close contacts who were tested was 7% (95% CI: 6.3–7.8%). The number of close contacts needed to test at 'day 0' to identify one case was 15, and 63 at 'day 7'.